2013
DOI: 10.1007/s10875-013-9870-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Pneumococcal Antibody Concentration and Avidity with Patient Clinical and Immunologic Characteristics

Abstract: Antibody concentration and avidity correlate with patient clinical characteristics and distinguish patients from controls. Measurement of antibody avidity may provide another dimension for the clinical assessment of pneumococcal polysaccharide antibody response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Furthermore, traditional ELISA methods may fail to detect low affinity interactions with fast dissociation rates and often EC 50 calculation is limited to a symmetrical sigmoid curve (using 4-parameter curve fitting) and data from non-symmetrical curves may be less reliable. Other indirect immunoassays for measuring binding strength include use of chaotropic or dissociating agents like diethylamine (Barkoff et al, 2012) or NH 4 SCN (Almanzar et al, 2013; Fried et al, 2013; Prelog et al, 2013). In this modified ELISA immmuoassay, a relative avidity index is calculated after dissociation of low avidity antibodies (Kneitz et al, 2004; Fried et al, 2013; Prelog et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, traditional ELISA methods may fail to detect low affinity interactions with fast dissociation rates and often EC 50 calculation is limited to a symmetrical sigmoid curve (using 4-parameter curve fitting) and data from non-symmetrical curves may be less reliable. Other indirect immunoassays for measuring binding strength include use of chaotropic or dissociating agents like diethylamine (Barkoff et al, 2012) or NH 4 SCN (Almanzar et al, 2013; Fried et al, 2013; Prelog et al, 2013). In this modified ELISA immmuoassay, a relative avidity index is calculated after dissociation of low avidity antibodies (Kneitz et al, 2004; Fried et al, 2013; Prelog et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Other indirect immunoassays for measuring binding strength include use of chaotropic or dissociating agents like diethylamine (Barkoff et al, 2012) or NH 4 SCN (Almanzar et al, 2013; Fried et al, 2013; Prelog et al, 2013). In this modified ELISA immmuoassay, a relative avidity index is calculated after dissociation of low avidity antibodies (Kneitz et al, 2004; Fried et al, 2013; Prelog et al, 2013). A notable caveat associated with assays that use dissociating agents is that antibodies that bind to conformational epitopes can be more easily dissociated from their bound complex due to changes in the epitope conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that memory B cell responses in young children to both the T cell-dependent antigen CTB and the T cell-independent antigen LPS following vaccination were significantly lower than those achieved after natural infection (17). Antibody avidity has been shown to be a correlate of immune memory and protective immunity in both infection and vaccination for other infectious diseases in children (28)(29)(30)(31). In this study, we evaluated the magnitude and duration of antibody avidity in both children and adults who received two doses of Dukoral, a heatand formalin-inactivated oral cholera vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some individuals with “protective” levels of pathogen-specific IgG antibody may nevertheless not be protected by virtue of producing an antibody with low avidity or low opsonophagocytic activity. 181,182 However, there are currently no accepted clinical criteria regarding normal vaccine response based on measurements other than specific serum IgG antibody concentration.…”
Section: Diagnosismentioning
confidence: 99%